(untitled) (Revista Brasileira Multidisciplinar, 2026)
This systematic review aimed to investigate the relationship between Restless Legs Syndrome (RLS) and sleep quality in children and adolescents. The goal was to understand the influence of RLS on sleep disorders in this age group and the need for early diagnosis and effective therapeutic approaches. Relevant studies were searched in databases using specific Boolean operators. Inclusion criteria included articles available for free, published in English, Portuguese, or Spanish, and cross-sectional, longitudinal, or cohort studies. Methodological evaluation was conducted using the Joanna Briggs Institute tool, considering the quality of the selected studies. Out of the 92 articles initially identified, 4 were deemed eligible for review. The heterogeneity of methods used in the reviewed studies was noted as a limitation, hindering robust comparative analyses. Most studies were observational, limiting the establishment of causal relationships between RLS and sleep disorders. Despite methodological limitations, the results emphasize the importance of specific interventions for managing RLS in children and adolescents, aiming to improve sleep quality and positively impact overall health and academic performance of these individuals. Future research should include longitudinal studies investigating genetic, environmental, and metabolic factors, as well as standardization of assessment methods and increased diverse samples to strengthen the validity of the findings.